The industrialization of Peruvian Native Cotton - Declercq-Pedraza, Ludwig (2017)
The objective of this study is to evaluate the technical feasibility to obtain high quality yarns from Peruvian native cotton. This cotton grows in the north coast of Peru and is characterized by being naturally pig-mented with colors such as cream, green, brown, purple, white and beige without being dyed. However, this cotton has some features such as short fiber and low torsional resistance which makes it impossible to spin it with conventional machinery; therefore, a machine specially adapted for the spinning process was used.